2016
DOI: 10.18632/oncotarget.13298
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic versus laparoscopic resection of gastric gastrointestinal stromal tumors: a multicenter study

Abstract: Despite endoscopic resection has been performed to treat gastric gastrointestinal stromal tumor (GISTs). However, the safety and long-term outcomes remains controversial. This study aims to compare the safety and surgical outcomes of endoscopic versus laparoscopic resection of gastric GISTs. A total of 335 patients that were pathologically confirmed with gastric GISTs (tumor size ≤ 3.5 cm) were surgically treated with endoscopic resection (endoscopic group) or laparoscopic resection (laparoscopic group) in thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 25 publications
1
21
0
Order By: Relevance
“…In this study, the fundus of stomach is the most common location of GISTs. In total, 96.9 % (189/195) and 99.5 % (194/195) of the included population were positive for CD117 and CD34, respectively, consistent with a previous report of a multicenter study performed in China 23 .…”
Section: Discussionsupporting
confidence: 90%
“…In this study, the fundus of stomach is the most common location of GISTs. In total, 96.9 % (189/195) and 99.5 % (194/195) of the included population were positive for CD117 and CD34, respectively, consistent with a previous report of a multicenter study performed in China 23 .…”
Section: Discussionsupporting
confidence: 90%
“…Concerning the postoperative outcomes, although some previous studies have shown that the incidence of postoperative complications was equivalent between the two groups, 32,34 Jeong et al . 29 revealed that the postoperative adverse events were more common in the LAR group than in endoscopic operation patients.…”
Section: Discussionmentioning
confidence: 89%
“…Among the remaining 68 reports, 58 were excluded on account of insufficient data and failure to meet the criteria. Finally, 10 publications 26–35 published from 2012 to 2018 were enrolled in our current meta‐analysis, as exhibited in Figure 1. All studies were conducted in either China (nine studies) or Korea (one study).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations